2008
DOI: 10.1007/s00264-008-0580-5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of routine magnetic resonance imaging in meniscal and ligamentous injuries of the knee: comparison with arthroscopy

Abstract: The aim of this study was to detect the accuracy of routine magnetic resonance imaging (MRI) done in different centres and its agreement with arthroscopy in meniscal and ligamentous injuries of the knee. We prospectively examined 70 patients ranging in age between 22 and 59 years. History taking, plain X-ray, clinical examination, routine MRI and arthroscopy were done for all patients. Sensitivity, specificity, accuracy, positive and negative predictive values, P value and kappa agreement measures were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 15 publications
4
41
1
Order By: Relevance
“…In a study in Mashhad on 92 patients with knee injuries, Mazlomy et al noted similar results and reported a high accuracy for clinical examinations [17]. Behairy et al is an Egyptian study of 70 patients that noted high diagnostic accuracy of both physical examination and MRI, and in most cases, only small differences existed between the two methods, which was also confirmed in a study by Thomas et al [5,18]. Major causes for the differences in the results were related to different skill levels of staff involved in MRI interpretation, arthroscopy and clinical examination.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In a study in Mashhad on 92 patients with knee injuries, Mazlomy et al noted similar results and reported a high accuracy for clinical examinations [17]. Behairy et al is an Egyptian study of 70 patients that noted high diagnostic accuracy of both physical examination and MRI, and in most cases, only small differences existed between the two methods, which was also confirmed in a study by Thomas et al [5,18]. Major causes for the differences in the results were related to different skill levels of staff involved in MRI interpretation, arthroscopy and clinical examination.…”
Section: Discussionsupporting
confidence: 68%
“…The injury to these intra articular structures is generally termed as " Meniscal tear and degeneration are manifested as increased signal intensity on T1 & T2 weighted images within the substance of meniscus. Meniscal abnormalities on MRI have been classified by grading system [5,6] into 4 grades as in figures 1-4. Clinical significant of intra meniscal signal uncertain, it likely that MRI is more sensitive than arthroscopy and the decision to perform menisectomy currently is based exclusively on the presence of a surface tear.…”
mentioning
confidence: 99%
“…Previous studies have reported an accuracy rate of over 90% using MRI to diagnose meniscal tears. [6][7][8][9][10][11][12][13] In a patient with an acute knee injury, the presence of pain and swelling prevents the clinician from performing an adequate physical examination.…”
mentioning
confidence: 99%
“…For example, finding the internal posterior angle tears of the meniscus and the lower and edge tears of the meniscus is generally difficult. Finally, a true positive can be misread as a false positive, which increases the false positive rate (Khanda et al, 2008;Behairy et al, 2009). The consequences of a false positive finding are serious and can cause unnecessary arthroscopy or arthrotomy, which increases operation pains and economic burden for patients.…”
Section: Discussionmentioning
confidence: 99%